Probabilistic decoding algorithm for quantum stabilizer codes - XIAO Fang-ying; CHEN Han-wu (Tongxin xuebao)
To improve the performance of quantum decoding algorithm,a quantum probabilistic decoding algorithm（QPDA） based on the check matrix for quantum stabilizer codes was proposed.To achieve low error rates the error op-erator with the minimum quantum weight was chosen and to shorten the time of decoding a quantum standard array（QSA） was constructed before decoding.Comparing with the quantum maximum likelihood decoding algorithm,the QPAD improves the reliability of degenerate decoding due to uniform decoding methods for degenerate and non-degenerate codes,furthermore,has less complexity due to does not require pre-search the bases of vector space cor-responding to the error operator.